A Class of Symmetric and Quadratic Utility Functions Generating Giffen Demand - LANDI, Massimiliano (Institutional Knowledge at Singapore Management University, 2015)
I provide a simple example of a quadratic utility function that generates a Giffen demand. The utility function is symmetric, increasing and concave. Interestingly, the Giffen effect arises in the subspace where the utility function is strictly increasing and strictly concave. A full characterization of the parameter conditions under which the Giffen demand arises is provided.